2021
DOI: 10.1002/advs.202102561
|View full text |Cite
|
Sign up to set email alerts
|

Trojan Horse‐Like Nano‐AIE Aggregates Based on Homologous Targeting Strategy and Their Photodynamic Therapy in Anticancer Application

Abstract: Photodynamic therapy (PDT) has become a promising candidate for cancer theranostics; however, traditional photosensitizers (PSs) usually exhibit weak fluorescence and poor reactive oxygen species (ROS) generation efficiency when aggregated. Recently, aggregation-induced emission (AIE) luminogens have shown great potential in the development of novel PSs owing to their excellent aggregation-induced ROS generation (AIG-ROS) activity. However, there are still concerns that must be addressed. In this study, two ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 44 publications
(57 reference statements)
0
32
0
Order By: Relevance
“…Interestingly, JC-1 staining demonstrated that TPE-Py-OH could still induce dramatically mitochondrial damage in spite of tending to accumulate into LDs in Figure 4D. Singlet oxygen species produced by PDT can oxidize intracellular LDs to form lipid oxide or lipid peroxide [50]. The intracellular lipid peroxidation could initiate cellular ferroptosis, which can induce mitochondrial morphology disruption and depolarization in this process [51].…”
Section: In Vitro Long-term Tracking and Pdt Of Tpe-py-ohmentioning
confidence: 99%
“…Interestingly, JC-1 staining demonstrated that TPE-Py-OH could still induce dramatically mitochondrial damage in spite of tending to accumulate into LDs in Figure 4D. Singlet oxygen species produced by PDT can oxidize intracellular LDs to form lipid oxide or lipid peroxide [50]. The intracellular lipid peroxidation could initiate cellular ferroptosis, which can induce mitochondrial morphology disruption and depolarization in this process [51].…”
Section: In Vitro Long-term Tracking and Pdt Of Tpe-py-ohmentioning
confidence: 99%
“…As a result, large amount of reactive oxygen species (ROS) would be produced, resulting in the break of redox balance within cancer cells 47 - 49 , elimination of overexpressed glutathione (GSH) and the inactivation of glutathione peroxidase 4 (GPX4) protein. These would aggravate the excessive accumulation of lipid oxidation (LPOs) and trigger cancer cells ferroptosis (Figure 3 A) 50 - 51 . To validate the above proposed process, the intracellular concentration of Zn 2+ for Zn-Fu MNs treatment cancer cells was detected by ICP-MS, which showed the distinct increased Zn 2+ within Zn-Fu MNs treatment cells compared with PBS group, proving the Zn-Fu MNs entered the cells, successfully ( Figure S5 ).…”
Section: Resultsmentioning
confidence: 99%
“…To validate the above proposed process, the intracellular concentration of Zn 2+ for Zn-Fu MNs treatment cancer cells was detected by ICP-MS, which showed the distinct increased Zn 2+ within Zn-Fu MNs treatment cells compared with PBS group, proving the Zn-Fu MNs entered the cells, successfully ( Figure S5 ). Subsequently, we tested the cellular ROS production via incubating CT26 cells with Zn 2+ , Fu and Zn-Fu MNs, respectively, using 2',7'-dichlorofluorescin diacetate (DCFH-DA) as ROS indicator (Figure 3 B) 51 . From confocal fluorescent images, obvious fluorescence in green channel was observed in Zn 2+ treatment cells, indicating the intracellular ROS generation induced by Zn 2+ .…”
Section: Resultsmentioning
confidence: 99%
“…Currently, three methods are existed for introducing heavy atoms, one of which is to introduce halogen atom via covalent bond. For example, Tang's group synthesized an AIE-active model PS (PI) with good ROS production efficiency and NIR emission capability [ 78 ]. To enhance the ISC process, a thiophene ring was inlet into the backbone of PI by the heavy atom effect to obtain PTI.…”
Section: Design Of Aie-pss For Pdtmentioning
confidence: 99%